CONSUMO ENERGÉTICO DE UM TRATOR AGRÍCOLA EM ÁREAS DE TRÁFEGO CONTROLADO - ASSUNÇÃO, Kennedy Alves; GOMIDES, João Flávio Floriano Borges; MARTINS, Murilo Battistuzzi; SERON, Cássio de Castro; VENDRUSCOLO, Eduardo Pradi (ANAIS DO ENIC, 2022)
-